Nivel de satisfacción de los usuarios en los servicios ofrecidos por BanEcuador – Sucursal Echeandía - Chingal Cerezo, Karen Scarleth (2019)
The present case study was found at the Banking Agency of Canton Echeandía. The purpose of this research is to evaluate the level of satisfaction of the bank's clients based on the services offered in the entity. This study is based on the parameters of the qualitative research methodology and the inductive method for a better analysis of the problems detected in the public banking institution. The results obtained from the investigation carried out in the banking entity are: excessive agglomeration of clients in sales, infrastructure of the reduced banking entity, excessive delay in the procedures of account opening and credit management, lack of ATMs, facilities inappropriate administrative areas